2008
DOI: 10.1097/mao.0b013e31817156df
|View full text |Cite
|
Sign up to set email alerts
|

Vibrant Soundbridge Versus Conventional Hearing Aid in Sensorineural High-Frequency Hearing Loss

Abstract: This prospective study demonstrated that direct-drive stimulation provided by the VSB allows better speech performances than acoustic stimulation for rehabilitation of patients with steeply sloping high-frequency hearing losses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 9 publications
3
37
0
2
Order By: Relevance
“…Because both devices used the same signalprocessing chip and provided equivalent amounts of gain, the authors attributed better performance and subjective device benefit and satisfaction with the AMEI to better sound fidelity provided by direct-drive stimulation of the ossicular chain. Comparable findings are reported by Truy et al (12) in patients with steeply sloping highfrequency hearing loss. Both groups used the same signalprocessing chip for their measurements, and the authors compared a true open-ear canal solution, namely an AMEI, with a conventional earmold-fit HA.…”
supporting
confidence: 82%
“…Because both devices used the same signalprocessing chip and provided equivalent amounts of gain, the authors attributed better performance and subjective device benefit and satisfaction with the AMEI to better sound fidelity provided by direct-drive stimulation of the ossicular chain. Comparable findings are reported by Truy et al (12) in patients with steeply sloping highfrequency hearing loss. Both groups used the same signalprocessing chip for their measurements, and the authors compared a true open-ear canal solution, namely an AMEI, with a conventional earmold-fit HA.…”
supporting
confidence: 82%
“…In a study comparing the VSB with conventional hearing aids in patients with a ski-slope type of hearing loss, Truy et al (17) found better speech perception in the subjects implanted with a Soundbridge. Because implantable systems have a lower susceptibility to device failure than the combination of a passive prosthesis with a conventional hearing aid, the implantable system is preferable especially in patients with mixed hearing loss.…”
Section: Discussionmentioning
confidence: 98%
“…The effectiveness of the system has previously been established [Fisch et al, 2001;Fraysse et al, 2001;Snik and Cremers, 2001;Sterkers et al, 2003;Todt et al, 2002;Uziel et al, 2003] and the performance of the VSB has been compared to conventional HAs in several studies [Boheim et al, 2010;Schmuziger et al, 2006;Snik and Cremers, 2001;Sziklai and Szilvassy, 2011;Todt et al, 2002;Truy et al, 2008Uziel et al, 2003. Since proven to be an alternative solution in individuals with moderate-to-severe SNHL, the so-called incus vibroplasty has become a routine clinical procedure.…”
Section: Introductionmentioning
confidence: 99%